2009
DOI: 10.1353/dem.0.0037
|View full text |Cite
|
Sign up to set email alerts
|

Predicting adult health and mortality from adolescent facial characteristics in yearbook photographs

Abstract: ongitudinal research in the social sciences has enriched our understanding of the antecedents and consequences of obesity (Crossman, Sullivan, and Benin 2006;Goodman and Whitaker 2002;Himes 2000;Mannino et al. 2006;Novak, Ahlgren, and Hammarstrom 2006;Sundquist and Johansson 1998). Unfortunately, for much of the twentieth century, social scientists did not routinely record the height and weight of study participants (but see, e.g., Ayres 1909). As a consequence, a number of important longitudinal studies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 39 publications
2
60
0
2
Order By: Relevance
“…Adolescent facial adiposity judgements are associated with all-cause mortality ( particularly heart disease mortality) and several medically assessed chronic conditions in a large longitudinal study (n ¼ 3027 [24]). Adiposity is also highly heritable [28], thus a person with an optimal level of adiposity could potentially provide not only direct, but also indirect benefits to a partner.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent facial adiposity judgements are associated with all-cause mortality ( particularly heart disease mortality) and several medically assessed chronic conditions in a large longitudinal study (n ¼ 3027 [24]). Adiposity is also highly heritable [28], thus a person with an optimal level of adiposity could potentially provide not only direct, but also indirect benefits to a partner.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that the RBM measure is a valid and reliable indicator of body mass (Glass et al 2010; Reither et al 2009). The RBM scale fares well with respect to interrater reliability (Cronbach's α = 0.91) and intrarater reliability, where test-retest correlations are 0.8 or higher for a majority of coders (Reither et al 2009). RBM in adolescence is also a significant predictor of BMI, obesity, and health outcomes in midlife (e.g., hypertension, diabetes and premature mortality), demonstrating excellent criterion-related validity.…”
Section: Methodsmentioning
confidence: 99%
“…Ratings were averaged across participants for each face. [18][19][20][21][22][23][24][25][26][27][28][29] were taken using a camera in D65 lighting in a photographic booth painted with spectrally neutral grey and colour reference card (Gregtag Macbeth Mini ColorChecker Pantone). Clothing was covered with a grey-coloured board to prevent coloured reflection from clothing affecting facial illumination.…”
Section: (Iii) Perceptual Ratingsmentioning
confidence: 99%